36.4k views
2 votes
Please Help!

Solve the system:

y = 4x − 19

y = −3x + 23

A
(5, 6)

B
(4, 1)

C
No Solution

D
(6, 5)

User Manticore
by
5.4k points

2 Answers

3 votes

Answer:

(6,5)

Explanation:

The two expressions are both equal to y, so they are equal to each other.

4x - 19 = -3x + 23

Add 3x to both sides.

7x - 19 = 23

Add 19 to both sides.

7x = 42

Divide by 7 to get x alone.

x = 6

Now find the y value by substituting x in an equation.

y = 4x - 19

y = 4(6) - 19 = 24 - 19 = 5

User SlimDeluxe
by
5.6k points
0 votes

Answer:

x=6 y=5

Explanation:

set the two equations equal to each other

User Pishpish
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.